2008
DOI: 10.1093/annonc/mdn183
|View full text |Cite
|
Sign up to set email alerts
|

The value of radiotherapy on metastatic internal mammary nodes in breast cancer. Results on a large series

Abstract: The 'regional nodal mapping', is a fundamental step to stage breast carcinoma. In addition to the axillary nodes status, the involvement of internal mammary nodes is an important prognostic factor. Six hundred and sixty-three patients with breast carcinoma, mainly in the inner quadrants, underwent a biopsy of internal mammary nodes. Positive internal mammary nodes were found in 68 out of 663 cases (10.3%) representing 27.2% of all cases with regional node metastases (250). When histologically proven metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 23 publications
3
66
1
1
Order By: Relevance
“…4,5 Elective irradiation of the regional nodes remained widely used until the late 1980s, when it became less popular on the basis of an overview of older trials that showed no survival benefit, despite improvement in control of locoregional disease. 6 There was even a suggestion of decreased long-term survival owing to irradiation of the heart. [5][6][7] However, some studies predicted a beneficial effect in patients who had a high risk of regional involvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Elective irradiation of the regional nodes remained widely used until the late 1980s, when it became less popular on the basis of an overview of older trials that showed no survival benefit, despite improvement in control of locoregional disease. 6 There was even a suggestion of decreased long-term survival owing to irradiation of the heart. [5][6][7] However, some studies predicted a beneficial effect in patients who had a high risk of regional involvement.…”
mentioning
confidence: 99%
“…6 There was even a suggestion of decreased long-term survival owing to irradiation of the heart. [5][6][7] However, some studies predicted a beneficial effect in patients who had a high risk of regional involvement. 8,9 Because of this controversy, many centers irradiated only the axilla and medial supraclavicular nodes in patients with risk factors and avoided the internal mammary nodes to protect the heart.…”
mentioning
confidence: 99%
“…Most of these patients would need adjuvant therapy such as chemotherapy and/or radiation and/or hormonal therapy. However, two recent European studies showed that IMN dissection improved accuracy of breast cancer staging and survival [35,36] . The patients with IMN metastases had a better 5-year survival after IMN radiotherapy and chemotherapy [34] .…”
Section: Fdg Pet/ct For Internal Mammary Lymph Nodesmentioning
confidence: 99%
“…IMN sampling was performed in 139 cases and metastasis were found in 31 (22%) cases (31/139) showing that patients with IMN drainage have a significant risk for metastasis. In contrast to this high positivity ratio, Veronesi et al 25 evaluated 663 breast cancer patients of whom 68 had metastasis in IMN (10.3%). Farrus et al 26 reported 14% positivity rate of IMN in patients with early stage breast cancer.…”
Section: Incidence Of Imn Drainage and Imn Metastasismentioning
confidence: 99%